Buoyancy induced heat transfer and fluid flow inside a tilted wavy solar collector - Varol, Yasin; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2007)
Natural convection heat transfer and fluid flow were investigated inside a wavy walled and inclined solar collector, numerically. Flat ceiling was considered as cover (cold temperature) of solar collector and wavy wall as absorber (hot temperature). CFDRC commercial code was used to solve laminar-governing equations of natural convection. Working fluid was considered as air with Pr = 0.71 inside the collector. Parameters that affect the flow and temperature field are Rayleigh number, inclination angle, aspect ratio, and wavelength. Flow and temperature fields were presented by streamlines and isotherms. Local and mean Nusselt numbers were calculated. Results indicate that heat transfer is increased with increasing Rayleigh number and aspect ratio, and is decreased with increasing wavelength. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: natural convection; wavy solar collector; inclined enclosure